Avoiding Cleavage of the Sternum: A Better Approach in Patients with Myasthenia Gravis - Ullah, Muhammad Kaleem; Ullah, Muhammad Sami; Rashid, Muhammad; Ali, Mansoor; Tariq, Ayesha (Biological and Clinical Sciences Research Journal, 2025)
Thymectomy is a well-established treatment for Myasthenia Gravis (MG), but the optimal surgical approach—median sternotomy versus Video-Assisted Thoracoscopic Surgery (VATS)—remains under debate. This study evaluates the outcomes of these approaches to determine the effectiveness and safety of avoiding midline sternotomy. Objective: To assess the clinical, pathological, and postoperative outcomes of thymectomy using VATS compared to median sternotomy in MG patients. Methods: A retrospective analysis was conducted on 173 MG patients who underwent thymectomy from July 2002 to June 2024 at a tertiary care center. Data on demographics, histopathology, surgical approach, WHO thymoma classification, Masaoka staging, and clinical outcomes were collected and analyzed. Preoperative optimization included 3–5 cycles of plasmapheresis. Results: Of the 173 patients, 108 underwent VATS thymectomy and 65 underwent sternotomy. Thymic hyperplasia was the most common histological finding. Thymomas were more prevalent in males and were primarily Type B2 under the WHO 2015 classification. Most thymomas were Stage I or II per Modified Masaoka staging. Complete remission was achieved in 30.1% of patients, palliation in 28.3%, no clinical change in 30.6%, while 2.9% succumbed to disease complications. VATS thymectomy was associated with reduced morbidity and better postoperative recovery. Conclusion: VATS thymectomy is a safe and effective surgical option for MG, offering improved clinical outcomes and reduced need for postoperative analgesia and ICU stay. Avoiding midline sternotomy enhances patient recovery and reduces complications, especially in resource-limited settings.